2012
DOI: 10.2298/sarh1208412t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soft tissue thickness in persons with malocclusions of class II division 1 and class II division 2

Abstract: The facial soft tissue profile indicated significant differences in the thickness dependant on the type of malocclusion and gender. Because of their great variability and a significant participation in the formation of the profile, while planning orthodontic therapy, it is necessary to pay them full attention, with obligatory analysis of the dentoskeletal profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…According to previously published research by Tanic et al, who compared FSTT using the same method as in the current study, they established that the thickest soft tissues in the area of the sulcus of the upper lip, upper and lower lip, showed significant differences between men and women [ 25 ]. In a further study by same authors, published a year later, they established significant differences in the area of the sulcus labrale superius and labrale inferius, with patients in Class II/2 having much greater values of FSTT compared with patients in Class II/1 [ 26 ]. With this distribution of soft tissue thickness, the retrusion of the upper and lower incisors and posterior position of dentoalveolar jaw segments was camouflaged, which is the basic morphological feature of this dental and skeletal relationship [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previously published research by Tanic et al, who compared FSTT using the same method as in the current study, they established that the thickest soft tissues in the area of the sulcus of the upper lip, upper and lower lip, showed significant differences between men and women [ 25 ]. In a further study by same authors, published a year later, they established significant differences in the area of the sulcus labrale superius and labrale inferius, with patients in Class II/2 having much greater values of FSTT compared with patients in Class II/1 [ 26 ]. With this distribution of soft tissue thickness, the retrusion of the upper and lower incisors and posterior position of dentoalveolar jaw segments was camouflaged, which is the basic morphological feature of this dental and skeletal relationship [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research from different parts of the world has shown that soft tissue thickness closely corresponds to sagittal malocclusions [ 9 , 14 , 24 – 28 ]. There is still controversy over the influence of sex on FSTT, and most authors believe that there are significant differences between men and women in FSTT [ 2 , 5 , 8 , 25 , 26 , 29 – 31 ]. However, other authors refute these differences [ 16 , 20 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the nose, can, to a minor or larger extent, influence the harmony of a profile overall [ 34 , 35 ], especially in persons with class II division 2, where there is already a protrusion of nose and subnasal area. In these persons, a small nose or a nose bent upwards, can camouflage the irregularity and contribute to softening of the “sharpness” of a profile [ 18 , 35 , 36 ]. By examining representation of different types of noses in both our study groups significant differences were not established ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive circumstance is that, in some analyses, statistical significance was not established, which points to two possible answers: 1) irregularity in certain segments of a dento-skeletal profile is less pronounced [ 7 ] and, 2) thickness of soft tissues of lips in class II division 2 is increased so that it camouflages a characteristic dento-skeletal profile form. Almost all the authors who have examined this issue agree with the second statement, since they established that soft tissues of a face, with its fullness, can act in two ways: if the face is thin, it emphasizes the listed marks of the existing malocclusion, or if the face is of a fuller-compensatory appearance, it masks the existing skeletal relationship [ 7 , 17 , 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation